Effect of Radiofrequency Ablation (RFA) on Cutaneous Manifestations of Varicose Vein - Shakya, Yagya Ratna; Karmacharya, Robin Man (Journal of Nepalgunj Medical College, 2019)
Introduction: The varicose vein is a common chronic vascular disease affecting people with predisposing factors like restricted mobility, pregnancy, obesity, and long-standing jobs. According to CEAP (Clinical, Etiological, Anatomical, and Pathological) classification, there are six categories of CEAP ranging from C0 or no sign to C6 or active ulceration of the vein. Radiofrequency Ablation (RFA) is the minimally invasive procedure to manage varicose vein. This study aims to assess cutaneous manifestation and quality of life among participants who underwent RFA in the Dhulikhel Hospital. Methodology: This study is retrospective review of the clinical and surgical report of 171 consecutive number of patients admitted with varicose veins and treated with Radio Frequency Ablation from January 2015 to December 2016. The cutaneous manifestation of all the patients were noted prior to surgery and were followed up in two months to note the manifestation again. Results: The total number of patients were171 with 79 male (46.2%) and 92 female (53.8%). The mean age was 48.9 years (S.D. 6.8). In pre-ablative stage, there were 42.1% patients in C4 stage, 30.4% patients in C3 stage, 16.4% in C2 stage. In post-ablative stage, there were 39.8% patients in C4 stage, 16.4% in C1 and 11.7% in C2 stage. In 53.8% of patients, there was a decrease in C stage postoperatively. Findings of this study are encouraging in terms of C staging after RFA, and it paves the way for further exploration of RFA.